Religious moderation curriculum in a global perspective - Dudun Najmudin; Asep Herry Hernawan; Laksmi Dewi; Lia Susanti; Ilham Pebrian (Inovasi Kurikulum, 2025)
This research is motivated by the rise of radicalism and intolerance in various parts of the world, which emphasizes the importance of education to promote religious moderation. Religious moderation curriculum is a solution to building a more inclusive and tolerant global society. This study aims to identify the application of religious moderation curriculum in various global contexts and evaluate its impact on forming moderate attitudes, interfaith dialogue, and social peace. This research uses a qualitative method with a systematic literature study. Data were collected from various appropriate and relevant articles to identify effective policies, approaches, and implementation strategies, as well as the development of a religious moderation curriculum. The results show that implementing the religious moderation curriculum has successfully encouraged tolerance, strengthened interfaith dialogue, and suppressed the potential for radicalism. However, some challenges are still faced, such as resistance from conservative groups and difficulties adapting the curriculum to be relevant to the local context without losing the essence of the universal values of moderation. The conclusion of this study underscores that religious moderation curricula have great potential to support global peace and promote harmonious diversity if implemented appropriately.   Abstrak Penelitian ini dilatarbelakangi oleh meningkatnya radikalisme dan intoleransi di berbagai belahan dunia, yang menekankan pentingnya pendidikan sebagai alat untuk mempromosikan moderasi beragama. Kurikulum moderasi beragama dipandang sebagai solusi dalam membangun masyarakat global yang lebih inklusif dan toleran terhadap perbedaan. Tujuan penelitian ini adalah untuk mengidentifikasi penerapan kurikulum moderasi beragama dalam berbagai konteks global dan mengevaluasi dampaknya terhadap pembentukan sikap moderat, dialog antaragama, serta perdamaian sosial. Penelitian ini menggunakan metode kualitatif dengan studi literatur sistematis. Pengumpulan data diambil dari berbagai artikel yang layak dan relevan untuk mengidentifikasi kebijakan, pendekatan, dan strategi implementasi yang efektif, serta pengembangan kurikulum moderasi beragama. Hasil penelitian menunjukkan bahwa penerapan kurikulum moderasi beragama berhasil mendorong sikap toleransi, memperkuat dialog antaragama, dan menekan potensi radikalisme. Namun, beberapa tantangan masih dihadapi, seperti resistensi dari kelompok konservatif dan kesulitan dalam mengadaptasi kurikulum agar relevan dengan konteks lokal tanpa kehilangan esensi nilai universal moderasi. Simpulan penelitian ini menggarisbawahi bahwa kurikulum moderasi beragama memiliki potensi besar dalam mendukung perdamaian global dan mempromosikan keberagaman yang harmonis apabila diterapkan secara tepat. Kata Kunci: kurikulum; moderasi beragama; perspektif global